Prevalensi kanker payudara subtipe triple negative pada wanita usia muda di Bali periode januari 2014 – oktober 2016 - Primadanti, Soraya Juventia; Setiawan, I Gede Budhi (E-Jurnal Medika Udayana; Vol 7 No 2 (2018): E-Jurnal Medika Udayana, 2018)
Background: Breast cancer in young women and triple negative subtype in breast cancer are often associated with poor prognosis including poor response to therapy, low life expectancy, and higher mortality rate. This study was conducted to determine the characteristics of triple negative subtype breast cancer in young women in Bali period January 2014–October 2016 based on histopathological, clinical stage, and grade diagnosis. Method: Descriptive method with cross-sectional design using secondary data from Cancer Registry in Bali. Breast cancer of young women patient samples are collected with the criteria of age ?40 years and have molecular triple negative subtype. Result: Of 123 samples collected, 26 samples obtained with triple negative subtype. Furthermore, the results show that of the 26 samples: (1) Eleven samples were from the age group 36 to 40 years; (2) Twenty-five samples of an invasive carcinoma of no special type; (3) Eight samples are stage IIIB with ten samples of any size tumor with direct extension to chest wall or skin (T4), eleven samples with metastasis in movable ipsilateral axillary lymph nodes (N1) and only two samples of distant metastasis (M1); (4) Nineteen samples with poorly differentiated tumor (grade III). Conclusion: The prevalence of triple negative breast cancer in young women in Bali period January 2014–October 2016 was 21.1% with the most common characteristics: age range 36 to 40, had invasive carcinoma of no special type, stadium IIIB, T4, N1, M0, and grade III. Keywords: Breast cancer, triple negative subtype, young women